PENINGKATAN PENGETAHUAN PERILAKU HIDUP BERSIH DAN SEHAT DI DESA CITANGTU KECAMATAN WANARAJA KABUPATEN GARUT - Aceng Ali Awaludin; Sulastini; K Dewi Budiarti; Gin Gin Sugih Permana; Andhika Lungguh Perceka; Eti Suliyawati (LP4M STIKes Karsa Husada Garut, 2022)
Healthy conditions, both physically, mentally, spiritually and socially which enable everyone to live productively socially and economically. The implementation of this activity has a direction to improve the clean and healthy life behavior of Citangtu Village residents. The method used in this community service activity cursed the lecture, counseling and practice techniques given to 40 residents of Citangtu Village, Wanaraja District, Garut Regency. This activity resulted in an increase in residents' knowledge of clean and healthy living habits, 22 Residents had very good knowledge and 18 people had good knowledge. The overview obtained, the enthusiasm of the residents was very high when the counseling was carried out it was hoped that the counseling and practice examples that were socialized could be applied in everyday life and carried out in a sustainable manner.